Solitary functioning kidney in high anorectal malformation - Kanishka Das; Srinivas Raju Rajkiran (Wolters Kluwer Medknow Publications, 2017)
Aim: A solitary functioning renal unit in high anorectal malformation may harbor anomalies in the upper/lower urinary tract that further compromise renal function and accelerate hyperfiltration injury. We aimed to analyze the clinical course, management, and outcome of children with a solitary renal unit and high anorectal malformation. Materials and Methods: A cohort of solitary renal units in anorectal malformation managed between 2000 and 2015 with a defined protocol at a pediatric nephro-urology clinic are included in the study. Investigations and management were individualized according to issues in the agenetic/dysplastic unit, solitary functioning unit, or bladder-urethra. Clinical details, management, and outcome were analyzed. Results: Of 53 cases of high anorectal malformation with urologic anomalies, 17 (32%) had single kidneys. Majority (10/17, 59%) had another complicating urinary tract anomaly, four being uremic at presentation. Nearly half had multiple urinary infections including epididymo-orchitis unrelated to the rectourinary fistula and warranted additional stoma (bowel/urinary) or other urinary tract surgery. At a mean follow-up of 70 months, majority (14/17, 82%) have a preserved solitary renoureteric unit while the remaining three await renal replacement therapy. Conclusion: Solitary functioning renal units associated with high anorectal malformation in children need meticulous investigation and surveillance to facilitate renal preservation. The implications of the associated rectourinary fistula, vesicoureteral reflux, urinary infections including epididymo-orchitis, and other urinary tract anomalies on the conventional surgical management are illustrated.